Performance and metagenomic analysis of a micro-aerated anaerobic reactor for biological sulfate-rich wastewater treatment. Issue 3 (June 2022) - Deng, Xue; Su, Chengyuan; Luo, Xiaoen; Liu, Xiaoyue; Liang, Zhu; Ding, Fengxiu; Yang, Wenjing; Xu, Yufeng; Chen, Menglin
Abstract: The start-up process, microbial communities, and metagenomic features of a micro-aerated anaerobic reactor for the treatment of sulfate wastewater were investigated. At a COD/SO4 2- ratio of 1.0 of the influent, the average COD, SO4 2- and NH4 + -N removal rate in the micro-aerated anaerobic reactor was 93.43%, 34.97%, and 28.88%, respectively. However, with the COD/SO4 2- ratio increased from 1.0 to 1.5, the average COD removal rate reduced by 15.55% and the average removal rate of SO4 2- increased by 2.85%. When the COD/SO4 2- ratio was 1.5, the activities of sulfite reductase, acetate kinase, and coenzyme F420 were highest in the sludge, with average concentrations of 0.12 Um/L, 0.089 mol/L, and 0.00913 mmol/g, respectively. During the whole experiment, the fluorescence peak of coenzyme F420 appeared in the LB-EPS, while the peaks of tryptophan-like protein and tyrosine-like protein appeared in TB-EPS. Proteobacteria was the main phylum in all three stages, with relative abundances of 28.17%, 22.74%, and 19.94%, respectively. Methanosaeta was the main genus, with relative abundances of 8.98%, 5.64%, and 7.08%, respectively, in stages A, B, and C. Meanwhile, the relative abundance of the dissimilatory sulfate reduction modules was 0.0083%, 0.0189%, and 0.0115%, which ensured the removal of sulfate in the micro-aerated anaerobic reactor. Graphical Abstract: ga1 Highlights: A micro-aerated anaerobic reactor was constructed. Average SO4 2- removal rate was 34.97% at COD/SO4 2- ratio of 1.0. Syntrophobacter was the dominant sulfate-reducing bacteria in the reactor. It was more conducive to glycolysis and nitrogen metabolism at COD/SO4 2- ratio of 1.